A thematic analysis exploring the experiences of bereaved caregivers undergoing a novel culinary grief intervention - Chow, Melissa Yan Zhi (Nanyang Technological University, 2024)
In Singapore, food is such a culturally salient part of life that many suggest its significance extends to situations surrounding death and could be utilised to support individuals to heal from their grief. However, existing literature concerning such interventions in the context of bereaved caregivers is sparse. Hence, this study sought to explore the experiences of bereaved caregivers who have undergone a culinary grief intervention, and the ways in which the intervention were deemed helpful during their grieving journey. The qualitative data used was collected as part of a larger project, The Table to Console: A Novel Psychotherapeutic Culinary Grief Intervention (CGI), where 23 bereaved caregivers aged between 21 and 70 participated in the intervention. Participants underwent the four-session programme which contained cooking activities, grief-oriented psychoeducation components, and meditation sessions that were followed by a single focus group discussion. Braun and Clarke’s thematic analysis approach was utilised to analyse the data and four major themes surrounding the participants’ experiences of the intervention were identified: Reminiscing the Deceased, Finding Camaraderie, Psychological Safety, and Personal Growth. The findings revealed insightful nuances on potential underlying mechanisms which could explain the effectiveness of the intervention but warrant further research and exploration. They also provided preliminary evidence of the untapped potential of culinary-based grief interventions to be used with bereaved individuals in Singapore. Overall, this study provided a significant contribution to the understanding of CGI, paving the way for the continued development of CGI as an alternate modality of grief support for bereaved individuals.